Digitisation in agriculture as a factor of competitiveness - Muñiz Espada, Esther; Gamazo Chillón, Juan Carlos (Przegląd Prawa Rolnego, 2020)
The authors underlie the qualitative and quantitative importance of agriculture and the agro-industrial sector in the Spanish economy analysed in the light of existing legal regulations and claim that a further development of the agricultural sector will only be possible when new information technologies and the Internet are implemented. Their application is one of the main challenges for the agro-industrial sector in the near future. These challenges justify posing questions about legal regulations on issues such as the ownership and storage of data that relate to the application of new technologies, access to, transfer and circulation of these data, the exchange of data through Internet platforms and the control over these platforms, the responsibility thereof, forms of doing business in the context of the application of new technologies, or, as seems to be the most important, cyber-security.